2014
DOI: 10.1007/s11914-014-0235-y
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Glycolysis in Osteoblasts

Abstract: Osteoblasts, the chief bone-making cells in the body, are a focus of osteoporosis research. Although teriparatite, a synthetic fragment of the human parathyroid hormone (PTH), has been an effective bone anabolic drug, there remains a clinical need for additional therapeutics that safely stimulates osteoblast number and function. Work in the past several decades has provided unprecedented clarity about the roles of growth factors and transcription factors in regulating osteoblast differentiation and activity, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 64 publications
0
48
0
Order By: Relevance
“…Osteoblasts appear to metabolize glucose mostly into lactate even in the presence of sufficient oxygen, a process known as aerobic glycolysis [20]. The phenomenon was documented initially in bone explants and later in isolated osteoblasts [16,2123].…”
Section: Glucose Metabolism In Osteoblastsmentioning
confidence: 99%
“…Osteoblasts appear to metabolize glucose mostly into lactate even in the presence of sufficient oxygen, a process known as aerobic glycolysis [20]. The phenomenon was documented initially in bone explants and later in isolated osteoblasts [16,2123].…”
Section: Glucose Metabolism In Osteoblastsmentioning
confidence: 99%
“…65 Studies from independent laboratories have confirmed that osteogenic differentiation is driven almost exclusively by glycolysis and that GLUT1 is essential to that process. 66,67 Moreover, PTH, which can enhance HSC egress and MSC differentiation, works by inducing glycolysis in differentiated osteoblasts, probably through upregulation of GLUT1 and GLUT3 expression. 68 Overall, it is clear that the bioenergetics of cells in the niche, driven by ATP demand, help determine how specific transcriptional factors induce the differentiation of stem and progenitor cells.…”
Section: Biochemistry Of the Nichementioning
confidence: 99%
“…Glucose is the primary fuel for remodeling; osteoblasts rely on glucose as their primary energy source [48,49] and osteoclasts also use glucose [42].…”
Section: Bone Structure and Function Are Dependent On Insulin And Glumentioning
confidence: 99%